Clinical, etiological and antimicrobial susceptibility profile of pediatric urinary tract infections in a tertiary care hospital of Nepal - Lok Bahadur Shrestha; Ratna Baral; Prakash Poudel; Basudha Khanal (BMC, 2019)
Abstract Background Urinary tract infection (UTI) is one of most common pediatric infections. The study was designed to assess the clinical profile, common bacterial microorganisms causing UTI and their antimicrobial susceptibility patterns at B. P. Koirala Institute of Health Sciences (BPKIHS) hospital. Methods This is a prospective cross-sectional study conducted at Department of Microbiology and Infectious Diseases for 6 months (January to June 2018). A total of 1962 non-repetitive urine specimens (midstream, nappy pad, catheter aspirated) of pediatric patients (0-14 years age) suspected of UTI were obtained in the Microbiology laboratory. Clinical data was obtained from requisition form and hospital software. Culture and bacterial identification was done by using standard microbiological guidelines. Antimicrobial susceptibility testing was done by Kirby-Bauer disc diffusion method following clinical and laboratory standards institute (CLSI) guidelines. Resistance to methicillin and vancomycin were confirmed by calculating minimum inhibitory concentration using broth dilution method. Results Among 1962 samples, 314 (16%) were positive for bacterial infection. Fever, irritability and poor feeding was the most common symptoms in neonates while older children presented with fever and urinary symptoms. E. coli was reported the most common etiological agent (53%), followed by Enterococcus faecalis (22%), Klebsiella pneumoniae (7%) and Staphylococcus aureus (7%). Multidrug resistant (MDR) isolates accounted for 32% of isolates, while 5% were extensively drug resistant (XDR). Fourty percentage of gram-negative bacilli were ESBL producer, 38% of S. aureus were methicillin resistant Staphylococcus aureus (MRSA) and 5% E. faecalis were vacomycin resistant enterococci (VRE). E coli was highly resistant to Ampicillin (87%), Ceftriaxone (62%) and Ofloxacin (62%). Amikacin (11% resistance) and Nitrofurantoin (5% resistance) are the most effective drugs for gram-negative bacilli (GNB) while vancomycin and linezolid are functional against gram-positive cocci. Conclusions High-level antimicrobial resistance was observed in pediatric UTI with alarming incidence superbugs like MDR, XDR, ESBL and MRSA. Regular surveillance should be carried out to determine the local prevalence of organisms and antimicrobial susceptibilities in order to guide the proper management of children.